A Study of the History, Style and Identity in Musical Practices of the Celestial Church of Christ - Faseun, Oluwafemi (2015)
The study investigated the historical sources of various forms of music used in the Celestial Church of Christ, the styles as well as the major features and performance practices that characterised the music. It identified the major contributors to its growth and development and also examined the performance styles and context. This was with a view to explicating the sociological and cultural factors that enhanced the growth of music in the Celestial Church of Christ.